CAN FOREIGN DIRECT INVESTMENT REDUCE UNEMPLOYMENT IN HOME COUNTRIES? ANALYSIS FOR ASEAN COUNTRY - Elsa Widia; Endrizal Ridwan; Fajri Muharja (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Direct Foreign Investment (FDI) has been considered as one of the important strategies in long-term economic evelopment. FDI is seen not only as a capital transfer but also has an important effect on increasing the host economy. FDI then became popular in many countries, so it was interesting to analyze the effects produced, both positive and negative. This research focuses on countries in the Association of Southeast Asian Nations (ASEAN) with the aim of conducting empirical studies on opportunities for employment creation by FDI. However, due to limited data in several countries, this study only involved Indonesia, Singapore, Malaysia and Thailand. The type of data used in this study is annual data covering from 1980-2017. Using estimation Vector Error Correction Model (VECM) allows to see short-term and long-term effects. The test results prove that the influence between variables is more visible in the long run.